Engineering the Amine Transaminase from Vibrio fluvialis towards Branched‐Chain Substrates. Issue 20 (15th September 2016) - Genz, Maika; Melse, Okke; Schmidt, Sandy; Vickers, Clare; Dörr, Mark; van den Bergh, Tom; Joosten, Henk‐Jan; Bornscheuer, Uwe T.
Abstract: Chiral amines are important building blocks, especially for the pharmaceutical industry. Although amine transaminases (ATAs) are versatile enzymes to synthesize chiral amines, the wildtype enzymes do not accept ketones with two large substituents next to the carbonyl functionality. Using bioinformatic tools to design a seven‐site mutant library followed by high‐throughput screening, we were able to identify variants of the enzyme from Vibrio fluvialis (VF‐ATA) with a widened binding pocket, as exemplified for a range of ketones. Three variants allowed the asymmetric synthesis of 2, 2‐dimethyl‐1‐phenylpropan‐1‐amine—not accessible by any wildtype ATA described so far. The best variant containing four mutations (L56V, W57C, F85V, V153A) gave 100 % conversion of the ketone to yield the amine with an enantiomeric excess value >99 %, notably with preference for the ( R )‐enantiomer. In silico modeling enabled the reconstruction of the substrate binding mode to the newly evolved pocket and, hence, allowed explanation of the experimental results. Abstract : If you know what amine : On the basis of bioinformatic analysis of the binding site of amine transaminases, a seven‐site combinatorial library of the enzyme from V. fluvialis is created. High‐throughput screening of this library leads to the identification of enzyme variants able to convert sterically demanding ketones into the corresponding chiral amines with high to excellent optical purities and yields.